A fuzzy mixed-integer linear programming model for aircraft maintenance workforce optimization - TUZKAYA, GÜLFEM; KILIÇ, HÜSEYİN SELÇUK (My University, 2023)
Aircraft maintenance is a labor-intensive process. Hence, the majority of studies in this field focus on improving labor productivity and working conditions. Since airplanes have complex structures, the automation of their maintenance is still in its early stage. Workforce optimization is critical for both increasing airworthiness and efficient use of operator fleets. Therefore, efficient and experienced technicians are indispensable for MRO companies. This paper aims to prevent occupational accidents and TAT delays by assigning critical maintenance tasks to experienced technicians. Moreover, the rules of the authorities and the priorities of cards are also taken into account in the model and a shift-based mixed integer linear programming assignment model is created. A fuzzy rule-based system is used to determine the values of some parameters within the proposed mathematical model. Finally, the model is applied to an MRO company in Türkiye, and the data sets provided are analyzed.
Keywords: Bilgi Sistemleri, Haberleşme ve Kontrol Mühendisliği; Kontrol ve Sistem Mühendisliği; Sinyal İşleme; Mühendislik ve Teknoloji; Information Systems, Communication and Control Engineering; Control and System Engineering; Signal Processing; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Mühendislik; OTOMASYON & KONTROL SİSTEMLERİ; TELEKOMÜNİKASYON; MÜHENDİSLİK, ELEKTRİK VE ELEKTRONİK; Engineering, Computing & Technology (ENG); ENGINEERING; AUTOMATION & CONTROL SYSTEMS; TELECOMMUNICATIONS; ENGINEERING, ELECTRICAL & ELECTRONIC; Fizik Bilimleri; Bilgisayar Ağları ve İletişim; Control and Systems Engineering; Physical Sciences; Computer Networks and Communications; Fuzzy Rule-Based Approach; Maintenance Planning; Mixed-Integer Linear Programming; Workforce Optimization